RITUAL RUWATAN MURWAKALA DALAM RELIGIUSITAS MASYARAKAT JAWA - Dewi Ayu Wisnu Wardani (Widya Aksara, 2020)
Ruwatan Murwakala is a ritual tradition that is still preserved by most Javanese people. Javanese society is a society that is rich in treasures and traditions from the ancestors and with this the Javanese people have to maintain Javanese culture. Javanese values ??are stored behind ritual symbols, while some Javanese are no longer able to read and understand the language of these symbols. As a result, Javanese rituals such as Ruwatan Murwakala are increasingly distant from his heir. Ruwatan ceremony is a Javanese traditional ceremony full of meaning. However, explanations and studies that are able to bridge the ritual to the people of Java so far have not understood. The puppet show with the Murwakala play is a depiction of the growth and development of the catastrophe (crime, destruction) and extinction. In order to ward off the threat of the safety of human life, Dalang Kandhabuwana needs to be shown, namely the depiction of Bhatara Vishnu who has the authority to deal with all the disasters waged by Bhatara Kala. Dalang Kandhabuwana is an authorized force and serves as a savior of human life by "breaking" the ferocity of Bhatara Kala. Therefore the Murwakala play is also called the Dhalang Kandhabuwana (murwakala, mastering Bhatara Kala) or Kanalangaru Dhalang. In the traditional ruwatan accompanied by puppet performances. Puppeteer Kandhabuwana is a protector and savior of the world who acts with all excellence: (1) Kandhabuwana is a speaker of the nature of life, (2) is wise and wise, (3) able to read the Kalachakra rajah, (4) can master the Bhatara Kala, and (5) purifier of any interference that threatens humans. Murwakala which to support various participants has various meanings in cultural life and human safety, among others (1) Murwakala ritual ceremony is a sacred custom, (2) Murwakala ruwatan is a pasemon (pralambang) which contains instructions on ceremonies regulating human survival, namely that humans avoid evil (destruction) should be willing to learn about the nature of life through wisdom and policy as illustrated by the qualities of the Dalang Kandhabuwana (Bhatara Vishnu). In a series of ruwatan rituals, Rajah Kalachakra is a way back, it contains a mantra as a repellent or disaster for human safety.